Malay Sufism: An Analysis of Sufistic Behavior among the Uluan and Iliran Clans in South Sumatra: Sufisme Melayu : Analisis Perilaku Sufistik Marga Uluan dan Iliran di Sumetera Selatan - Nico Oktario Adytyas; M Sirajudin Fikri (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2021)
This study aims to analyze how Malay Sufism manifests as sufi-oriented conduct among the Uluan and Iliran clans in South Sumatra and why the Uluan–Iliran dichotomy shapes distinct patterns of religiosity, social ethics, and spiritual practice in modern contexts. Using a qualitative approach, primary and secondary data were collected through interviews, observation, and documentation, then thematically analyzed to map living sufi values, practices, and symbols embedded in customary life and social relations. Findings indicate that differences between Uluan and Iliran are grounded not only in culture but also in their interpretations of tasawuf as adab, self-restraint, humility, and social piety sustained through inherited traditions and local authority. The study implies that Malay Sufism can serve as an ethical bridge accommodating custom, religion, and civic life, strengthening religious moderation and inclusive social order. Its originality lies in treating Sufism as a concrete socio-cultural practice across two local communities within a Malay setting, contributing new insights to Sufi studies, anthropology of religion, and local studies